A herbal formula comprising Rosae Multiflorae Fructus and Lonicerae Japonicae Flos inhibits the production of inflammatory mediators and the IRAK-1/TAK1 and TBK1/IRF3 pathways in RAW 264.7 and THP-1 cells. (4th November 2015) - Cheng, Brian Chi Yan; Yu, Hua; Su, Tao; Fu, Xiu‐Qiong; Guo, Hui; Li, Ting; Cao, Hui-Hui; Tse, Anfernee Kai-Wing; Kwan, Hiu-Yee; Yu, Zhi-Ling
Abstract: Ethnopharmacological relevance: As documented in the Chinese Materia Medica Grand Dictionary (中藥大辭典), a herbal formula (RL) consisting of Rosae Multiflorae Fructus (multiflora rose hips) and Lonicerae Japonicae Flos (Japanese honeysuckle flowers) has traditionally been used in treating inflammatory disorders. RL was previously reported to inhibit the expression of various inflammatory mediators regulated by NF-κB and MAPKs that are components of the TLR4 signalling pathways. Aim of the study: This study aims to provide further justification for clinical application of RL in treating inflammatory disorders by further delineating the involvement of the TLR4 signalling cascades in the effects of RL on inflammatory mediators. Materials and methods: RL consisting of Rosae Multiflorae Fructus and Lonicerae Japonicae Flos (in 5:3 ratio) was extracted using absolute ethanol. We investigated the effect of RL on the production of cytokines and chemokines that are regulated by three key transcription factors of the TLR4 signalling pathways AP-1, NF-κB and IRF3 in LPS-stimulated RAW264.7 cells using the multiplex biometric immunoassay. Phosphorylation of AP-1, NF-κB, IRF3, IκB-α, IKKα/β, Akt, TAK1, TBK1, IRAK-1 and IRAK-4 were examined in LPS-stimulated RAW264.7 cells and THP-1 cells using Western blotting. Nuclear localizations of AP-1, NF-κB and IRF3 were also examined using Western blotting. Results: RL reduced the secretion of various pro-inflammatory cytokines and chemokines regulated by transcription factors AP-1, NF-κB and IRF3. Phosphorylation and nuclear protein levels of these transcription factors were decreased by RL treatment. Moreover, RL inhibited the activation/phosphorylation of IκB-α, IKKα/β, TAK1, TBK1 and IRAK-1. Conclusions: Suppression of the IRAK-1/TAK1 and TBK1/IRF3 signalling pathways was associated with the effect of RL on inflammatory mediators in LPS-stimulated RAW264.7 and THP-1 cells. This provides further pharmacological basis for the clinical application of RL in the treatment of inflammatory disorders. Graphical abstract: